PENGARUH KUALITAS PRODUK KUALITAS LAYANAN DAN PERSEPSI HARGA TERHADAP LOYALITAS MELALUI KEPUASAN - Cholis Annasir, 13.05.51.0112 (Students Journal of Economic and Management, 2017)
The purpose of this study was to determine the effect of direct and  indirect service quality, trust, corporate image, and  customer satisfaction as an intervening variable on loyalityThe population of this research is the customers to the store jenang karomah in kudus.The total sample 100 respondents with purposive sampling. Data obtained by the questionnaire. This research variable quality produk  (X1) servie  (X2),price (X3), customer satisfaction (Y1), and loyality (Y2).             The result of the research indicated that the quality product (X1), service (X2), price (X3) show that there are influance bigger than loyality(Y2) trough customer satisfaction.                The conclusion from the study of the quality product (X1), service (X2), price (X3) effect on loyalty (Y2) through satisfaction (Y1) .It is suggested to Toko Jenang Karomah to improve quality product, In the belief Toko Jenang Karomah should be able to increase the trust of its members and on corporate image should Toko Jenang Karomah able to show stability. Keyword :Product Quality, service, price, satisfaction and loyalty